Symbiotic nitrogen fixation : (Science Publishers ( SP ), 2004)
Based on the proceedings of the Biological Nitrogen Fixation for Increased Crop Productivity, Enhanced Human Health and Sustained Soil Fertility, this book takes a holistic approach to harnessing legume BNF technologies, starting from a socioeconomic perspective and progresseing to agronomic and genetic options.